Enhancing the Quality of Education Through Implementation Free Tutoring for Elementary School Students At the Learning House & Private Belia Education Padang - Stavinibelia Stavinibelia; Gusnita Efrina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
The implementation of this community service discusses the activity of providing free tutoring to several elementary school students at the Lubuk Buaya Education & Private Learning House, Padang City. The purpose of this activity is to provide free learning to elementary school students and to help them repeat what they learned at school. The number of participants in this activity was 5 elementary school students. The results of this activity include increasing student learning motivation, so that children are able to complete homework problems without having to argue with their parents. The outputs resulting from this free tutoring activity are: Journals with ISSN; The services of this free tutoring activity can increase students' motivation and confidence in learning and provide additional knowledge for participants and can help children continue to study at home without having to be reprimanded from their respective parents